Evaluation of indicators of honey of different origin - Sviatnenko, Roman; Marynin, Andriy; Poznyak, Oksana (My University, 2023)
Recently, the development of the Ukrainian honey market creates opportunities for the development of agriculture and increasing the income of beekeepers. In particular, the increase in honey production can contribute to the development of other industries, such as the cosmetic and pharmaceutical industries, where honey is an important component. In general, the prospects for the development of the Ukrainian honey market are considered quite promising and favorable for the economic development of the country. The work is devoted to research on the determination of organoleptic and physicochemical parameters of honey of various origins. It was established that all experimental samples of honey (buckwheat, sunflower, floral and linden) meet the requirements of DSTU 4497:2005 "Natural honey. Technical conditions" (State standard of Ukraine) and are of high quality.
Keywords: honey; physical and chemical indications; diastasis number of Gothe; мед; фізико-хімічні показники; діастазне число Готе